Cancer stem cells in lung cancer: Evidence and controversies. Issue 5 (21st June 2013) - Alamgeer, Muhammad; Peacock, Craig D.; Matsui, William; Ganju, Vinod; Watkins, D. Neil
Abstract The cancer stem cell (CSC) model is based on a myriad of experimental and clinical observations suggesting that the malignant phenotype is sustained by a subset of cells characterized by the capacity for self‐renewal, differentiation and innate resistance to chemotherapy and radiation. CSC may be responsible for disease recurrence after definitive therapy and may therefore be functionally synonymous with minimal residual disease. Similar to other solid tumours, several putative surface markers for lung CSC have been identified, including CD133 and CD44. In addition, expression and/or activity of the cytoplasmic enzyme aldehyde dehydrogenase ALDH and capacity of cells to exclude membrane permeable dyes (known as the 'side population') correlate with stem‐like function in vitro and in vivo. Embryonic stem cell pathways such as Hedgehog, Notch and WNT may also be active in lung cancers stem cells and therefore may be therapeutically targetable for maintenance therapy in patients achieving a complete response to surgery, radiotherapy or chemotherapy. This paper will review the evidence regarding the existence and function of lung CSC in the context of the experimental and clinical evidence and discuss some ongoing controversies regarding this model.